Modifying and Validating a Quality of Life Measure to Fit Your Patient Population - Michelle Johnson; J Maclean; Rebecca Rogers; Donna Fick; Andre Kallab (Georgia Southern University, 2007)
Introduction: A well-developed quality of life (QoL) instrument is valuable in identifying the burden of illness. We were interested in exploring whether existing QoL instruments were suitable for patients in our medical setting and, if not, whether this could be rectified by adapting an existing valid and reliable instrument to meet the specific needs of our patient population. For the purposes of this study, we chose to evaluate the quality of life of patients with breast cancer. Specifically, we were interested in two aspects of QoL in women with breast cancer. The first was whether existing instruments were pertinent to the women in our venue. The second research interest was dependent upon the first. If current instruments were found wanting, could this be rectified through the creation and validation of new domains of relevance to these patients? Method: First, five patients were interviewed to ascertain QoL issues pertinent to women in our medical setting. Second, to determine regional appropriateness of existing breast cancer QoL instruments, a search was conducted to identify and review existing breast cancer specific QoL instruments. Third, an addendum was created (to be used in conjunction with an existing instrument identified through the search) that contained three QoL domains not typically found: Financial, Spirituality and Satisfaction with Medical Care. The addendum was then tested along with an existing instrument (FACT-B). Results: Internal consistency for the new scales, Satisfaction with Medical Care, Spirituality, and Financial had alpha coefficients of 0.81, 0.80, and 0.63 respectively. The total score for FACT-B plus addendum was 0.69. Pearson's correlation coefficients were 0.49 for Financial, 0.64 for Satisfaction with Medical Care, and 0.70 for Spirituality. Total test/retest was 0.71.